Consecutive lynestrenol and cross-sex hormone treatment in biological female adolescents with gender dysphoria: a retrospective analysis - Tack, Lloyd J. W. (Biol Sex Differ, 2016)
BACKGROUND: Prior to the start of cross-sex hormone therapy (CSH), androgenic progestins are often used to induce amenorrhea in female to male (FtM) pubertal adolescents with gender dysphoria (GD). The aim of this single-center study is to report changes in anthropometry, side effects, safety parameters, and hormone levels in a relatively large cohort of FtM adolescents with a diagnosis of GD at Tanner stage B4 or further, who were treated with lynestrenol (Orgametril®) monotherapy and in combination with testosterone esters (Sustanon®). METHODS: A retrospective analysis of clinical and biochemical data obtained during at least 6 months of hormonal treatment in FtM adolescents followed at our adolescent gender clinic since 2010 (n = 45) was conducted. McNemar’s test to analyze reported side effects over time was performed. A paired Student’s t test or a Wilcoxon signed-ranks test was performed, as appropriate, on anthropometric and biochemical data. For biochemical analyses, all statistical tests were done in comparison with baseline parameters. Patients who were using oral contraceptives (OC) at intake were excluded if a Mann-Whitney U test indicated influence of OC. RESULTS: Metrorrhagia and acne were most pronounced during the first months of monotherapy and combination therapy respectively and decreased thereafter. Headaches, hot flushes, and fatigue were the most reported side effects. Over the course of treatment, an increase in musculature, hemoglobin, hematocrit, creatinine, and liver enzymes was seen, progressively sliding into male reference ranges. Lipid metabolism shifted to an unfavorable high-density lipoprotein (HDL)/low-density lipoprotein (LDL) ratio; glucose metabolism was not affected. Sex hormone-binding globulin (SHBG), total testosterone, and estradiol levels decreased, and free testosterone slightly increased during monotherapy; total and free testosterone increased significantly during combination therapy. Gonadotropins were only fully suppressed during combination therapy. Anti-Müllerian hormone (AMH) remained stable throughout the treatment. Changes occurred in the first 6 months of treatment and remained mostly stable thereafter. CONCLUSIONS: Treatment of FtM gender dysphoric adolescents with lynestrenol monotherapy and in combination with testosterone esters is effective, safe, and inexpensive; however, suppression of gonadotropins is incomplete. Regular blood controls allow screening for unphysiological changes in safety parameters or hormonal levels and for medication abuse.